Sejarah Perkembangan Peradaban Islam di Mesir - Abu Haif (Universitas Islam Negeri Alauddin Makassar, 2015)
Egypt was a province of moslem when Umayyah and Abbasiyah empire still exist in Arab. Egypt was an important province, because there is so much Islamic civilation. In history, so many empires was conrolled by the Egypt. One of the empire was exist in Egypt is Fathimiyah. Fathimiyah was an important empire, it can be seen by a lot of sciences had develop in North Africa and became a center of Islamic civilization development. Beside it, there was an empire had ever contolled Egypt, it was Mamluk. Mamluk Empire controlled Egypt and survived from Mongol’s attack when Abbasiyah Empire in Baghdad had fallen. It means Mamluk was powerful. Before Mamluk, Ayyubiyah controlled Egypt. Shalahuddin al-Ayyubi was a famous leader and founder this empire. When Shalahuddin became a leader, he could got back Yerussalem to be a Moslem Empire.